ЭЛЕКТРИЧЕСКИЕ И ОПТИЧЕСКИЕ СВОЙСТВА СОЛНЕЧНОГО ЭЛЕМЕНТА С НАНОГЕТЕРОПЕРЕХОДАМИ - Имамов, Э.З.; Аскаров, М.А.; Исмайлов, К.А. (SCIENCE and SOCIETY, 2023)
The article question is considered of using non-crystalline silicon as a substrate of an effective solar cell. It is shown that the creation of an effective solar cell from non-crystalline silicon is possible only at high densities of localized defective energy states in the depth of the silicon band gap. It is shown that a particularly effective conversion of solar energy into electricity is possible when two materials are combined as components of heterojunctions: non-crystalline silicon and lead chalcogenides in the nano-dimensional state. It is shown that especially lead chalcogenides are characterized by a strong manifestation of the effects of multi-exciton generation and carrier multiplication.